Mastering matlab 7 - Hanselman, Duane C.; Littlefield, Bruce L. ([S.l.] : Prentice Hall, 2004)
This book covers all essential aspects of MATLAB presented within an easy-to-follow "learn while doing" tutorial format. Discussees all new features of the latest release of MATLAB. Discusses integration of MATLAB with C, FORTRAN, AND Java; increases MATLAB's power and flexibility in dealing with external algorithms, datasets, and operating system capabilities. Offers thorough coverage of indexing, vectorizing, and linear algebra. Features abundant examples throughout and includes a chapter that specifically covers extensive examples. Includes a comprehensive index. A useful reference for engineers or anyone who uses MATLAB.